2016
DOI: 10.1002/2016gl068854
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the ionization coefficient of simulated iron micrometeoroids

Abstract: The interpretation of meteor radar observations has remained an open problem for decades. One of the most critical parameters to establish the size of an incoming meteoroid from radar echoes is the ionization coefficient, β, which still remains poorly known. Here we report on new experiments to simulate micrometeoroid ablation in laboratory conditions to measure β for iron particles impacting N2, air, CO2, and He gases. This new data set is compared to previous laboratory data where we find agreement except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…Given these inconsistencies, it was suggested that lowering β by one or two orders of magnitude would bring the radar measurements into better agreement with the ZDC model. However, the first results of this facility (reported in Thomas et al 1 ) showed that β is most likely not a significant factor in the discrepancy.…”
Section: A Motivation and Importancementioning
confidence: 81%
See 3 more Smart Citations
“…Given these inconsistencies, it was suggested that lowering β by one or two orders of magnitude would bring the radar measurements into better agreement with the ZDC model. However, the first results of this facility (reported in Thomas et al 1 ) showed that β is most likely not a significant factor in the discrepancy.…”
Section: A Motivation and Importancementioning
confidence: 81%
“…Recently, Thomas et al 1 reported the first scientific results from the ablation facility described in this article. That work measured the ionization coefficient of iron particles impacting N 2 , air, CO 2 , and He, and compared the new experimental values to a commonly used analytical theory 3 and past experimental work.…”
Section: Inroductionmentioning
confidence: 86%
See 2 more Smart Citations
“…An electrostatic dust accelerator has recently been used to generate metallic particles with velocities of 10-70 km s −1 , which are then introduced into a pressurized chamber where the particle partially or completely ablates over a short distance. The deceleration is used to determine the rate of mass loss, and an array of biased electrodes above and below the ablation path collect the ions and electrons produced along the ablation path, from which the ionization efficiency can be determined (Thomas et al 2016(Thomas et al , 2017. A model like CABMOD can then be used to calculate the height profile of the injection rates of the meteoritic constituents into a planetary atmosphere.…”
Section: Meteoric Ablationmentioning
confidence: 99%